Tribes of Consumption. Towards Self-segmentation Consumer - Ortiz Esaine, Nicolás Martín (2018)
The following article seeks to understand the consumer from a viewpoint of the tribes of consumption. In turn, position itself as a new alternative methodology for market research companies as an innovative approach to segmentation. Field explorations visits are exposed to various tribes’ consumption of Lima. In total we dive in nine cultural communities: skaters, gamers, surfers, k-popers, athletics, hipsters, otaku, music lovers and graffiti artists. We focus first on society and kindred relationship. In second hand, its features and applications of marketing. The article concludes with a reflection on key elements of the criterion of consumer segmentation tribes.